2007
DOI: 10.1080/02786820701213511
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influence on Vapor-and Particle-Phase Polycyclic Aromatic Hydrocarbon Concentrations in School Communities Located in Southern California

Abstract: The authors thank the respective school districts participating in the Children's Health Study (California Air Resources Board Contract A033-186) for their cooperation and use of facilities. We also thank Steven Barbosa and Pablo Cicero-Fernandez for helpful discussions and insights. This research was supported by the Southern California Particle Center and Supersite (US EPA Grants #R827352-01-0 and CR-82805901). Although the research described in this article has been funded wholly or in part by the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The DTT values averaged 0.14 (± 0.02 SEM) nmol/min/ m 3 , suggesting that ambient levels of chemical components contributing to the activity were very similar. This observation is consistent with previous studies which have shown that vapor-phase levels of quinones, the likely contributors to vapor-phase redox activity, do not significantly vary with season (Eiguren-Fernandez et al 2007; Eiguren-Fernandez et al 2004). …”
Section: Resultssupporting
confidence: 93%
“…The DTT values averaged 0.14 (± 0.02 SEM) nmol/min/ m 3 , suggesting that ambient levels of chemical components contributing to the activity were very similar. This observation is consistent with previous studies which have shown that vapor-phase levels of quinones, the likely contributors to vapor-phase redox activity, do not significantly vary with season (Eiguren-Fernandez et al 2007; Eiguren-Fernandez et al 2004). …”
Section: Resultssupporting
confidence: 93%
“…This observation lends support to the idea that elevated levels were due to a specific input(s) disrupting typical environmental conditions, and not simply a shift in partitioning between the vapor and aerosol phase. 56-58 A study performed in Oregon on the Willamette River in the Portland Harbor Superfund found dissolved OPAH concentrations in water ranging from 6 ng/L to 50 ng/L. 34 This observation by O'Connell et al .…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the available studies were conducted with different approaches, variation of the considered PAH congeners, and often PAHs analysed in different PM fractions (mainly in coarse fraction, or even unspecified); all of these further complicate the comparisons between the reported findings. As for data available for PM 2.5 -bound PAHs, Eiguren-Fernandez et al (2007) reported total concentrations of 15 compounds in a range of 0.4-1.8 ng m −3 in indoor air of schools in Southern California. Analyzing the same 15 PAHs, Krugly et al (2014) found much higher levels of PM 2.5 -bound PAHs (20.1-131 ng m −3 )in indoor air of schools in Lithuania.…”
Section: S1mentioning
confidence: 99%
“…Data available for primary schools (i.e. children 6-11yearsold)comefromafew European studies (Alves et al, 2014;Carpente and Bushkin-Bedient, 2013;Cirillo et al, 2006;Jovanović et al, 2014;Krugly et al, 2014;Moshammer and Neuberger, 2003;Romagnoli et al, 2014), Asia (Jyethi et al, 2014;Ruchirawat et al, 2006Ruchirawat et al, , 2007Tuntawiroon et al, 2007) and USA (Eiguren-Fernandez et al, 2007). However, the majority of those were typically conducted in a limited number of schools (typically 1-2 schools; only two known studies used a greater number of schools, namely 5 and 6; Krugly et al, 2014;Romagnoli et al, 2014), often situated just in one/same type of environment.…”
Section: Introductionmentioning
confidence: 99%